1986
DOI: 10.1002/j.1460-2075.1986.tb04460.x
|View full text |Cite
|
Sign up to set email alerts
|

The bacteriophage T4 gene for the small subunit of ribonucleotide reductase contains an intron.

Abstract: The bacteriophage T4 gene nrdB codes for the small subunit of the enzyme ribonucleotide reductase. The T4 nrdB gene was localized between 136.1 kb and 137.8 kb in the T4 genetic map according to the deduced structural homology of the protein to the amino acid sequence of its bacterial counterpart, the B2 subunit of Escherichia coli. This positions the C‐terminal end of the T4 nrdB gene approximately 2 kb closer to the T4 gene 63 than earlier anticipated from genetic recombinational analyses. The most surprisin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
57
0

Year Published

1986
1986
2009
2009

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(62 citation statements)
references
References 44 publications
5
57
0
Order By: Relevance
“…It contains stoichiometric amounts of a nonheme iron center and a tyrosyl free radical which are essential for activity (38). These characteristics are typical of other eucaryotic and viral ribonucleotide reductases and are similar to those of the enzymes from Escherichia coli and phage T4 (30,39).…”
supporting
confidence: 56%
“…It contains stoichiometric amounts of a nonheme iron center and a tyrosyl free radical which are essential for activity (38). These characteristics are typical of other eucaryotic and viral ribonucleotide reductases and are similar to those of the enzymes from Escherichia coli and phage T4 (30,39).…”
supporting
confidence: 56%
“…Both are highly homologous to the host enzymes. The phage genes possess an important distinguishing feature: nrdB (131) and nrdD (14) contain introns.…”
Section: Eukaryotesmentioning
confidence: 99%
“…It was recently demonstrated that the gene encoding the small subunit of the bacteriophage T4 ribonucleotide reductase (nrdB) contains an intron (Gott et al, 1986;Sjoberg et al, 1986). There is a high degree of similarity between this intron and eukaryotic introns, suggesting a common ancestry.…”
Section: Pseudogene Structuresmentioning
confidence: 99%